La punition commune du crime : la prison et l’amende à Montréal de 1845 à 1913 - Tremblay, Pierre; Therriault, Guy (Criminologie, 1985)
Common jails “produce” more punishment than either penitentiaries or reformatories for juvenile delinquents. Students of incarceration, however, have hitherto overlooked the significance of what could be called “petty” or minor punishment. Montreal's penal archives (1845-1913) have been systematically analyzed so as to permit a preliminary theory of such petty punishment institutions, their junction in the general penal economy and their evolution over time.